2011
DOI: 10.1074/jbc.m111.280990
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Rac3 GTPase in the Regulation of Autophagy

Abstract: The process of autophagy is situated at the intersection of multiple cell signaling pathways, including cell metabolism, growth, and death, and hence is subject to multiple forms of regulation. We previously reported that inhibition of isoprenylcysteine carboxylmethyltransferase (Icmt), which catalyzes the final step in the post-translational prenylation of so-called CAAX proteins, results in the induction of autophagy which enhances cell death in some cancer cells. In this study, using siRNA-mediated knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…14 On the other hand, we have found that RAC1 but not CDC42 is also involved in the regulation of the autophagic pathway, but it has an inhibitory role. Consistently, in a paper recently published by Zhu and collaborators 43 it has been demonstrated, using a siRNA approach, that RAC3 but not the RAC1 or RAC2 isoforms, has an inhibitory effect on autophagy. These differences in isoform requirement are likely due to the cell lines used.…”
Section: Discussionsupporting
confidence: 68%
“…14 On the other hand, we have found that RAC1 but not CDC42 is also involved in the regulation of the autophagic pathway, but it has an inhibitory role. Consistently, in a paper recently published by Zhu and collaborators 43 it has been demonstrated, using a siRNA approach, that RAC3 but not the RAC1 or RAC2 isoforms, has an inhibitory effect on autophagy. These differences in isoform requirement are likely due to the cell lines used.…”
Section: Discussionsupporting
confidence: 68%
“…We show here that Rac1 inhibition is essential for autophagic flux during starvation and potentially other stimuli (Zhu et al., 2011). Active Rac1 and LC3 compete for binding on neighboring domains in Armus.…”
Section: Discussionsupporting
confidence: 52%
“…Of the Rho family GTPases, Rac3 is implicated in regulating cell adhesion, growth, differentiation, and autophagy [38]. To date, little is known regarding the molecular regulation of Rac3 stability.…”
Section: Discussionmentioning
confidence: 99%